The Role of Field Facilitators in the Community-Based Drinking Water and Sanitation Program (Pamsimas) in Manjuto Jaya Village, Air Manjuto Sub-District, Mukomuko District - Rachman, Denny A.; Leonanda, Benny Dwika (Peneliti.net, 2023)
The Pamsimas Development, which is one of the government programs aimed at improving access to drinking water and sanitation, is funded by the state budget allocated to specific regions. Implemented since 2008, Pamsimas has had a positive impact on communities scattered across villages and urban areas, especially in meeting the needs for drinking water, sanitation, and promoting health behavior changes. Currently, Pamsimas is considered a flagship program for the development of drinking water and sanitation supply systems in rural and urban areas, aiming to increase the number of residents who can access drinking water and sanitation services. The program also seeks to enhance the adoption of clean and healthy living values and behaviors, with the goal of achieving 100% access to drinking water and sanitation by 2024. Pamsimas is viewed as a strategic step in improving community access to drinking water and sanitation, with a community-based approach that emphasizes empowerment and sustainability as key factors for success. The role of Field Facilitators (FF) is crucial in maintaining the quality and success of the PAMSIMAS program implementation. Close collaboration with relevant stakeholders, local governments, and the community is essential to effectively achieve program objectives. In the implementation of PAMSIMAS development, discrepancies between proposed plans and actual realization often occur, highlighting the need for the role of Technical Implementing Officers (Field Facilitators) in rationalizing planning outcomes for PAMSIMAS development.